Chronic Spontaneous Urticaria and Sjögren's Syndrome: case report (Research, Society and Development, 2021)
Introduction: Chronic Spontaneous Urticaria (CHU) is characterized by transient papules, angioedema, or both for more than six weeks. CHU may be associated with Sjögren's Syndrome (SS). Purpose: This was to describe a clinical case of a patient diagnosed with Chronic Autoimmune Urticaria, with no improvement with standard treatment. Methodology: This case study was conducted in a qualitative, descriptive, observational and retrospective way, by direct patient data collection through access to medical records and exams. Case description: Female patient, 34 years old, referred for rheumatologic evaluation with UCE. In the search for secondary causes for CHU, she presented investigational tests with laboratory abnormalities. In addition, she also complained of dry symptoms. The exams concluded that this was a case of CHU associated with SS. After treatment of the underlying rheumatic disease, he presented improvement of the urticarial lesions. Discussion: In the reported case the lesions were refractory even after introduction of antihistamine treatment. Some scientific evidence suggests higher refractory rates to the standard treatment of UCE in those patients who present with immune-mediated events. In addition to the picture suggestive of UCE, the patient manifested dry symptoms. Normally, clinical manifestations do not occur simultaneously, which was not seen in this patient since she presented with concomitant pictures. Conclusion: The case portrays the typical occurrence of CHU associated with SS and highlights the importance of a good history taking and physical examination. In addition, it draws attention to the association between UCE and other immune-mediated diseases.